Health Monitoring and Personalized Feedback using Multimedia Data - Briassouli, Alexia; Benois-Pineau, Jenny; Hauptmann, Alexander; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book presents how multimedia data analysis, information retrieval and indexing are central for comprehensive, personalized, adaptive quality care and the prolongation of independent living at home. With sophisticated technologies in monitoring, diagnosis, and treatment, multimodal data plays an increasingly central role in healthcare. Experts in computer vision, image processing, medical imaging, biomedical engineering, medical informatics, physical education and motor control, visual learning, nursing and human sciences, information retrieval, content based image retrieval, eHealth, information fusion, multimedia communications and human computer interaction come together to provide a thorough overview of multimedia analysis in medicine and daily life.
Overview of Multimedia Data in Medical Applications -- 3D Craniofacial Image Analysis -- Visual medical analysis: Mammographic mass description for breast cancer recognition -- Video Analysis for Diagnosis of Neurodegenerative Disease: Development, Debugging and Assessment of PARKINSONCHECK Attributes through Visualisation -- Meaningful Bags of Words for Medical Image Classification and Retrieval -- Multimedia Information Retrieval from Ophthalmic Digital Archives -- Characterization of Data Quality in Electronic Healthcare Records -- Activity Detection and Recognition of Daily Living Events -- Recognition of Instrumental Activities of Daily Living in Egocentric Video for Activity Monitoring of Patients with Dementia -- Combining Multiple Sensors for Event Recognition of the Elderly -- Context-Aware Multimedia Recommenders In Health-Related Applications: The use of visual feedback techniques in balance rehabilitation -- Recommending Video Content for Use in Group-Based Reminiscence Therapy -- Personalised Mobile Health Feedback Using Ontologies for Managing User Profiles in Personalised Mobile Service Delivery -- A Cognitive Assistive System for Monitoring the Use of Home Medical Devices.
Keywords: Computer vision; Information systems; Image Processing and Computer Vision; Information Systems and Communication Service; Signal, Image and Speech Processing